Exosomes play roles in sequential processes of tumor metastasis. Issue 7 (4th November 2018) - Li, Keyu; Chen, Yonghua; Li, Ang; Tan, Chunlu; Liu, Xubao
Abstract : Overwhelming evidence demonstrates that exosomes, a series of biologically functional small vesicles of endocytic origin carrying a variety of active constituents, especially tumor‐derived exosomes, contribute to tumor progression and metastasis. This review focuses on the specific multifaceted roles of exosomes in affecting sequenced four crucial processes of metastasis, through which cancer cells spread from primary to secondary organs and finally form macroscopic metastatic lesions. First, exosomes modulate the primary tumor sites to assist cancer growth and dissemination. In this part, five main biological events are reviewed, including the transfer of oncogenic constituents, the recruitment and activation of fibroblasts, the induction of angiogenesis, immunosuppression and epithelial‐mesenchymal transition (EMT) promotion. In Step 2, we list two recently disclosed mechanisms during the organ‐specific homing process: the exosomal integrin model and exosomal epidermal growth factor receptor (EGFR)/miR‐26/hepatocyte growth factor (HGF) model. Subsequently, Step 3 focuses on the interactions between exosomes and pre‐metastatic niche, in which we highlight the specific functions of exosomes in angiogenesis, lymphangiogenesis, immune modulation and metabolic, epigenetic and stromal reprogramming of pre‐metastatic niche. Finally, we summarize the mechanisms of exosomes in helping the metastatic circulating tumor cells escape from immunologic surveillance, survive in the blood circulation and proliferate in host organs.